Biomass yield and quality of the Miscanthus × giganteus in northern China. (22nd February 2022) - Wang, Ye; Wang, Hongbin; Li, Runzhi; Fan, Xifeng; Peng, Zhen; Wu, Juying; Duan, Liusheng
Abstract: Miscanthus × giganteus has attracted much attention and occupied a significant niche as a bioenergy crop to meet the world's energy demand and in the fight against climate change. In this study, a field experiment was conducted to evaluate the yield and biomass characteristics of M. × giganteus over a period of three years from 2013 to 2015 in Beijing, China. M. × giganteus plants showed higher tiller density and litter leaf weight in the third year, whereas no significant difference in plant height was observed among the years. In contrast, a larger number of nodes per plant were recorded in the first year. Biomass yield potential was the highest in the third year (42.3 t ha −1 ). In addition, plant height ( r = .594, p = .042), tiller density ( r = .854, p < .01), and number of nodes per plant ( r = ‐.589, p = .044) were significantly correlated with biomass yield. Contents of cellulose and lignin were higher in stems, while that of hemicellulose and ash were higher in leaves. M. × giganteus biomass may be used for cellulosic ethanol conversion due to high cellulose and hemicellulose contents and low lignin content and for direct combustion and co‐combustion due to high calorific value (18.5 MJ kg −1 ). To conclude, our findings indicate that M . × giganteus can be cultivated in northern China as an excellent herbaceous bioenergy crop. Rational utilization of the agronomic characteristics would be helpful to screening and breeding bioenergy grass for promoting bioenergy production in China. Core ideas: Miscanthus × giganteus is suitable for cultivation in northern China. Agronomic traits were significantly correlated with biomass yield. Biomass yield of M . × giganteus increased over a period of three years. Biomass quality exhibited better suitability for ethanol production. High calorific value may be used for direct combustion and co‐combustion.